Pengaruh Kepemilikan Manajerial, Leverage dan Kualitas Laba Terhadap Nilai Perusahaan - Katarina Lusi; Vinus Maulina; Rita Indah Mustikowati (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
This study aims to examine the effect of managerial ownership, leverage and earnings quality on firm value. The population in this study was taken from companies with basic and chemical industries in the Indonesia Stock Exchange period 2017-2018. The sampling technique in this study used purposive judgment sampling and obtained 28 company samples. Testing the hypothesis in this study using multiple linear regression analysis techniques. The results of this study indicate that: (1) managerial ownership influences company value. (2) leverage has no effect on firm value. (3) earnings quality has no effect on firm value.